A Reflective Account of Facilitating Teachers’ Professional Learning in Two Different Lesson Study Settings - Evrim Erbilgin; Jennifer M. Robinson (Education Sciences)
Lesson study is a school-based, collaborative professional learning model that typically involves teachers and a facilitator as key participants. It is important to develop insights into the role of the facilitators, as they have a supportive and crucial role in the lesson study process. This study examines the challenges and successes perceived by a facilitator when supporting lesson study in two different contexts in Abu Dhabi. A qualitative research design was employed for an in-depth focus on the journey of the facilitator in the lesson study process. Four teachers from a public school and three teachers from a private school completed lesson study following the collaborative lesson research model. The same facilitator worked with both groups. Data were collected through reflection journal entries written by the facilitator. Thematic analysis was utilized to make sense of the data, develop codes, and identify the following five themes: school leadership support, facilitator’s experience in lesson study, facilitator’s role in the lesson study process, teachers’ ownership of lesson study, and lesson study contributing to teachers’ knowledge and practice. Implications of the findings are discussed in the paper.